Emergency finder / Mohd Najib Ismail - Ismail, Mohd Najib (2016)
In this study, GPS tracking is becoming the most popular used to navigate to the destination in real time on the maps such as hospital. GPS and satellite communication are used to identified the area. Mostly GPS is used for outside environment, but it's depend on the satellites which communicate to the server and make it less ineffective for inside environment. The technology can define current location of the object through coordinates. Latitude and longitude will determine the current location of the object and can view through the maps which require internet connection. Thus, this technology was helpful use a lot in such a way. In emergency situation, this project develops to help the user find the nearby emergency location such as hospital to minimize their finding time. For completed this project, waterfall model is used in methodology such as analysis, requirements, design, evaluation, implementation, testing and development. The prototype was tested with several existing applications in the market to test the efficiency and functionality.